Análise da Angiopoietina-2 em pacientes com anemia falciforme: associação com uso de hidroxiureia, biomarcadores de hemólise e dano renal - Nascimento, Eliziane Souza (2025)
Sickle cell anemia (SCA) is a hemoglobinopathy characterized by chronic hemolytic anemia associated with recurrent vaso-occlusion crises in the microcirculation. Such events are responsible for the processes of systemic inflammation and endothelial damage, favoring the pro- angiogenic state. Facts that contribute to the clinical complexity of the disease and to the occurrence of damage to multiple organs, especially the kidneys. Among the events mentioned above, angiogenesis is the least described condition, as well as its relationship with the therapy used in the disease, hemolytic condition and increased risk of renal damage. Therefore, the study of angiogenic biomarkers, such as Angiopoietin-1 (Ang-1), Angiopoietin-2 (Ang-2) and VEGF in the context of the pathophysiology of the disease as well as its relationship with therapy, hemolysis and renal damage, becomes relevant. The objective of the study was to evaluate Ang- 2 in patients with SCA and associate it with the use of hydroxyurea (HU), hemolysis and risk of renal damage. This is a cross-sectional, observational, and analytical study with 76 patients with SCA, at baseline, of both sexes, undergoing outpatient follow-up at HEMOCE, Fortaleza, Ceará. A control group (CG) consisted of 24 blood donors from the aforementioned blood center. Data such as sex, age, use of HU, reticulocyte count, lactate dehydrogenase (LDH), and bilirubin were obtained from medical records. Peripheral blood and urine were collected for creatinine (serum and urinary) and proteinuria measurements by colorimetric method, albuminuria by immunoturbidimetry, estimated glomerular filtration rate (eGFR) by means of the CKD-EPI equation and Ang-2 by means of sandwich immunoenzymatic assay; the risk of CKD was assessed by the KDIGO risk table (2024). P<0.05 was considered significant in the associations and p<0.20 in the multivariate logistic regression. Patients with SCA had a median age of 29.5 years, 42 (55.3%) were female, 65 (85.5%) used HU, median albuminuria of 44.1 mg/g-Cr, 29 (43.9%) had low risk of CKD. Serum Ang-2 levels were increased compared to the control group (p < 0.001). We did not find significant differences in serum Ang-2 levels in patients with SCA, in relation to the use of HU. There was also no significant difference for hemolysis markers (Reticulocytes, LDH and Bilirubin), renal markers (albuminuria, eGFR) and risk of CKD in relation to the use or not of HU (p = 0.3). However, proteinuria was 163.3 mg/g-Cr in the group that used HU and 122.2 mg/g-Cr in the group without use (p = 0.047). Serum Ang-2 levels did not differ when stratified according to albuminuria values (<30 mg/g-Cr and ≥30 mg/g-Cr), but LDH, total (BT), direct (BD) and indirect (BI) bilirubin, proteinuria and albuminuria showed differences between groups (p<0.05). When verifying the association of Ang-2 levels with the risk of CKD, we observed that there was no difference between the groups (low, moderate and high risk). However, when analyzing only the high risk group for CKD, through logistic regression, we verified an association between Ang-2 and the increased risk of CKD (p<0.035), the same occurred for other variables such as age (p<0.096) and LDH (p<0.016). This study is unprecedented in that it explored, for the first time, the association between Angiopoietin-2 and sickle cell nephropathy, providing results that reinforce the theory that SCA presents a high pro- angiogenic state and that this is associated with the hemolytic condition and the development of renal complications. However, the beneficial effect of HU in this process was not evident. Prospective studies are recommended to obtain more robust results.